Re-imagining the ottoman past in Turkish politics: Past and present - (:unkn) unknown (My University, 2013)
The article analyses the use of Ottoman past as a central theme in Turkish politics since the 1960s. It discusses how the revivalist discourse treats the question of westernization and shapes the perception of young activists towards the Ottomans. As confrontational themes with the West surfaced more frequently, the search for a new "order" became more tangible. Furthermore, the negative outlook of the Republican historiography towards the Ottoman heritage was dismissed, especially among young and educated followers of the MHP and MSP-RP. This orientation gained more widespread acceptance among the mass during the AK Party years as a result of the government's revisionist foreign policy and increasing frequency of the references to the Ottoman history in the party leadership's discourse.